1999
DOI: 10.1002/(sici)1521-186x(199910)20:7<431::aid-bem4>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity caused by a nitric oxide synthase inhibitor is countered by ultra-wideband pulses

Abstract: Potential action of ultra‐wideband (UWB) electromagnetic field pulses on effects of NG‐nitro‐ L‐arginine methyl ester (L‐NAME), an inhibitor of nitric oxide synthase (NOS), on nociception and locomotor activity was investigated in CF‐1 mice. Animals were injected IP with saline or 50 mg/kg L‐NAME and exposed for 30 min to no pulses (sham exposure) or UWB pulses with electric field parameters of 102±1 kV/m peak amplitude, 0.90±0.05 ns duration, and 160±5 ps rise time (mean±S.D.) at 600/s. Animals were tested fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
1
10
1
1
Order By: Relevance
“…However, residual changes in baseline motor activity (as inferred by the numbers of midline chamber crossovers prior to context/shock pairings during the contextual fear conditioning paradigm) and for latencies to respond to thermal stimuli, were evident. Although motor activity and thermal analgesia are both affected by acute L-NAME administration, the vector of the effect appears to be influenced by animal strain (Seaman, Belt, Doyle, & Mathur, 1999). For instance, Moore, Oluyomi, Babbedge, Wallace, & Hart (1991) have reported that acute NOS inhibition dose-dependently (1-75 mg/kg) increased latencies in the formalin pain test while large doses of L-NAME (600 mg/kg) reduced baseline motor activity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, residual changes in baseline motor activity (as inferred by the numbers of midline chamber crossovers prior to context/shock pairings during the contextual fear conditioning paradigm) and for latencies to respond to thermal stimuli, were evident. Although motor activity and thermal analgesia are both affected by acute L-NAME administration, the vector of the effect appears to be influenced by animal strain (Seaman, Belt, Doyle, & Mathur, 1999). For instance, Moore, Oluyomi, Babbedge, Wallace, & Hart (1991) have reported that acute NOS inhibition dose-dependently (1-75 mg/kg) increased latencies in the formalin pain test while large doses of L-NAME (600 mg/kg) reduced baseline motor activity.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, Moore, Oluyomi, Babbedge, Wallace, & Hart (1991) have reported that acute NOS inhibition dose-dependently (1-75 mg/kg) increased latencies in the formalin pain test while large doses of L-NAME (600 mg/kg) reduced baseline motor activity. Seaman et al (1999) have demonstrated that the thermal latency (to back paw licks) following 50 mg/kg L-NAME increased by approximately 100% relative to untreated mice. This same dose of L-NAME increased motor activity (assessed by light beam interruptions in an open field environment) by approximately 20% relative to untreated mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While L-NAME was capable of inducing increased spontaneous activity in sham exposed mice, its effect was blocked entirely by the UWB exposure. In supporting the evidence that UWB pulses could affect nitric oxide production, Seaman et al [1999] referred to an enhanced nitric oxide production by 41 % in stimulated murine macrophages incubated with potassium nitrate (GLN treatment) after UWB exposure ]. The nitric oxide produced was 9.14 mM in sham-exposed and 12.89 mM in UWB-exposed GLN treated macrophages.…”
Section: Studies On the Biological Effects Of Ultra-wide-band Pulsessupporting
confidence: 64%
“…In an extension of their original study on morphine and UWB, Seaman et al [1999] studied the effects of a NOS inhibitor, N°-nitro-L-arginine methyl ester (L-NAME) on manifestation of UWB effects in CF-lTPlus. mice.…”
Section: Studies On the Biological Effects Of Ultra-wide-band Pulsesmentioning
confidence: 99%